2005
DOI: 10.1021/ja046114i
|View full text |Cite
|
Sign up to set email alerts
|

Thiolate Ligands for Synthesis of Water-Soluble Gold Clusters

Abstract: Water-soluble monolayer-protected gold clusters (MPCs) have been an object of investigation by many research groups since their first syntheses were reported in 1998 and 1999. The basic requirements for a ligand to form a monolayer protecting a gold cluster were established some time ago for alkanethiolate MPCs, but there has been no such information published for water-soluble MPCs. We identify 6 new ligands capable of forming water-soluble MPCs, as well as 22 water-soluble ligands that fail to form MPCs. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
156
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(164 citation statements)
references
References 19 publications
5
156
1
2
Order By: Relevance
“…[1][2][3] Key structural information for gold nanoparticles was recently obtained from the X-ray diffraction results of Jadzinsky et al with 1.1 Å resolution. 4 They found that adatom-bound RS-Au-SR-type "staple" bonding motifs cover the surface of an Au 79 core in the stable Au 102 (SR) 44 cluster; the stabilizing ligand SR used was S-C 6 H 4 -COOH derived from p-mercaptobenzoic acid (p-MBA), HSR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Key structural information for gold nanoparticles was recently obtained from the X-ray diffraction results of Jadzinsky et al with 1.1 Å resolution. 4 They found that adatom-bound RS-Au-SR-type "staple" bonding motifs cover the surface of an Au 79 core in the stable Au 102 (SR) 44 cluster; the stabilizing ligand SR used was S-C 6 H 4 -COOH derived from p-mercaptobenzoic acid (p-MBA), HSR.…”
Section: Introductionmentioning
confidence: 99%
“…These units are oriented with their nearly collinear S-Au-S atoms almost parallel to the core surface and their organic groups pointing outwards. Figure 1 shows an analogous structure in which this complex adsorbate is replaced with the methanethiyl (MT) radical SR = SCH 3 , maintaining the original RS-Au-RS head-group torsional angles; this modification allows the key structural features to be more easily visualized. The Au 79 gold core is also shown in Figure 1 and has pseudo D 5h…”
Section: Introductionmentioning
confidence: 99%
“…This feature is demonstrated by using the novel particle 2 in a well-known catalytic reaction. Its selectivity is superior to its polymer-supported analogue and only somewhat poorer than that of the soluble benzyl analogue (6). A catalyst designed like 2 is, however, being pursued for applications in e.g.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…The synthetic value lay in the possibility to differentiate the size of the gold core by precipitation. New applications have been made using the Brust-Schiffrin -protocol, including water-soluble particles 6 and other clusters, coated with simply functionalized small molecules (monolayerprotected). 7 Self-assembly of the layers on gold surface has also been reported, 8 as well as syntheses giving the opportunity to adjust the core size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation